2020
DOI: 10.1038/s41598-020-73461-x
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of medicinal fungus Taiwanofungus camphoratus reveals gene rearrangements and intron dynamics of Polyporales

Abstract: Taiwanofungus camphoratus is a highly valued medicinal mushroom that is endemic to Taiwan, China. In the present study, the mitogenome of T. camphoratus was assembled and compared with other published Polyporales mitogenomes. The T. camphoratus mitogenome was composed of circular DNA molecules, with a total size of 114,922 bp. Genome collinearity analysis revealed large-scale gene rearrangements between the mitogenomes of Polyporales, and T. camphoratus contained a unique gene order. The number and classes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 97 publications
2
11
0
Order By: Relevance
“…In the present study, we found the core PCGs [56] , [57] underwent non synonymous and synonymous mutations in Boletales, and different core PCGs showed differentiated mutation rate. The results were consistent with previous studies [58] , [59] . The rps3 gene was found differentiated greatly in Boletales species.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, we found the core PCGs [56] , [57] underwent non synonymous and synonymous mutations in Boletales, and different core PCGs showed differentiated mutation rate. The results were consistent with previous studies [58] , [59] . The rps3 gene was found differentiated greatly in Boletales species.…”
Section: Discussionsupporting
confidence: 94%
“…The rps3 gene is an ancient gene in fungi, which evolved within the endosymbiotic model and presents varied evolutionary routes (Korovesi et al, 2018 ). The rps3 gene was frequently observed to experience positive selection or relaxed selection in fungi (Wang et al, 2020b , c ), and the selection pressure on rps3 gene needs to be further verified. Most mitochondrial genes have been transferred to the nuclear genome during the evolution of eukaryotic lineages, which is considered to have many advantages (Bjorkholm et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, animal mitogenomes do not contain any introns, whereas plant mitogenomes mainly contain group II introns and fungal mitogenomes mainly contain group I introns 51,54 . The cox1 gene was found to be the main host gene of introns in mitogenomes of Basidiomycetes 55,56 . We divided the introns of cox1 genes of 14 Polyporales species into different position classes (Pcls) according to their insertion sites in the protein coding region.…”
Section: Mitochondrial Gene Rearrangement In Trametes Species Mitochondrial Gene Rearrangement Wasmentioning
confidence: 99%